The Use of Magazine in the Lyrics of D’bagindas’ Song “Empat Mata”: A Stylistic Study - Cahyaning Ridho Tulaini; Ali Imron Al-Ma’ruf (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Song lyrics are a person’s emotional expression or statement regarding things they have seen, heard or experienced. When conveying his experience, the poet uses figures of speech in the lyrics he creates. This research aims to describe the figures of speech contained in the lyrics of the song “Empat Mata” on the D’bagindas album. This research uses a descriptive qualitative approach with documentation techniques. The approach used by this research is a stylistic approach. Stylistic analysis is aimed at discussing the beauty of the content and the meaning of the use of figures of speech in a literary work. In general, there are 3 types of figures of speech. The comparative figures of speech found in the song “Empat Mata” include 1 personification, 1 metaphor, and 1 hyperbole. Meanwhile, the affirmative figures of speech include 4 pleonasms, 7 repetitions, and 3 ellipsis. Satire figures of speech include 3 sarcasms, irony is 2, and cynicism is 1. The research results also show that D’bagindas uses repetition figures of speech more, 7 data were found in the lyrics. The message contained in this song is quite deep, illustrating the importance of direct and face-to-face communication in relationships, especially when there are feelings and important things that you want to convey. This song also reflects feelings of love, longing and honesty in expressing one’s heart to someone special.